Peran dan intervensi pemerintah dalam perekonomian - Edy Suandi Hamid (Universitas Islam Indonesia, 1999)
It is widely accepted that government has an important role on economic development. Through policies on public sector for instance, government has a significant role in pushing economic growth. However, in economics literatures, there seems a debate about whether government should role on economic development.